Planning Theory and Planning Science in Practice: Everyday Work and Prospects for Regional Planners in Germany - Hellmich, Meike; Lamker, Christian Wilhelm; Lange, Linda (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
Spatial planning challenges increasingly cross local boundaries. Statutory planning, which is organized along all different levels of government, is very complex and with its mix of informal and formal instruments difficult to put into fixed categories. It acts between local self-autonomy and large-scale spatial changes. Available empirical evidence about how and whereby planning is currently done, is often unclear or weak. This article is grounded on a survey of practitioners within regional planning administrations in Germany to investigate the development and use of theories and the perspectives of practitioners on these theories. Theories and their understanding prove to be as diverse as practice itself. The challenge to translate scientific evidence into working progresses of practitioners, the understanding of theories and the self-perception of planning practitioners has also been addressed. One main aim of this article is to show perspectives on the daily work in practice, the transfer of expertise between research and practice, the emergence and use of theories as well as the perception of planning theories by practitioners. Results reveal a highly diverse landscape of planning practices and a duality between a vested interest in research evidence and planning theories, but also deficiencies in communication and mutual understanding.